Forensic evaluation of cervical spine distortion injuries in non-fatal road traffic accidents: An observational study - E. N. Travenko; V. A. Porodenko; S. A. Anuprienko; A. V. Аshkhotov; A. S. Penkin (Кубанский научный медицинский вестник, 2022)
Background. The study relevance is substantiated by the growing numbers of road vehicles and cervical spine traumas occurring among all spinal injuries. Currently, there is no common vision of the cervical trauma pathogenesis, diagnostic algorithm or treatment, which stipulates difficulties in the forensic evaluation of soft tissue injuries of the neck, especially combined with the head or spine traumas around neck, as well as certain diseases.Objectives. A study of the incidence of cervical spine distortion injuries and their clinical and forensic assessment for severity to human health.Methods. A retrospective selective single-stage trial and analysis of 32 forensic medical reports on road accident and physical injury administrative cases in 2017 (single year) have been conducted. Normally distributed data are presented as mean (M), standard deviation (SD) and percent shares. The significance of inter-share variation was estimated with Student’s t-test.Results. Cervical spine distortion injuries more frequently associated with traumas to drivers than passengers inside the salon (81.2%), especially in passenger vehicles, with front-seat travellers inflicted most often (60.0%). Cases of independent pathology were very rare. The most common were combinations with soft tissue injuries, combined blunt trauma to the head, torso and limbs, with craniocerebral or maxillofacial trauma. Cervical osteochondrosis was revealed in 18% cases. Primary diagnosis predominantly grounded on complaints and history (67%), with only 12% cases using a comprehensive neurological examination or instrumental methods. The severity was assessed in the context of concomitant injuries. Acute and moderate severity had equal rates of 6.2%, light severity — 37.5%, no damage — 9.3%. Non-qualified remained 39.8% cases due to a lack of full clinical and instrumental examination (66.7%) or the victim’s failure to appear (13.3%); 20% cases were expert-reported as uncertain for trauma circumstances and mechanism.Conclusion. Further research and systematisation of the data accumulated are necessary. The following clinical and forensic evaluation, as well as statistical analyses will facilitate common diagnostic and severity assessment algorithms to develop for mechanical soft tissue and ligament injuries of the cervical spine.